2020
DOI: 10.1007/s11187-020-00383-3
|View full text |Cite
|
Sign up to set email alerts
|

Designing for sustainable work during industrial startups—the case of a high-growth entrepreneurial firm

Abstract: New firms face challenges regarding pace, time, scalability, and societal changes, requiring increased attention to sustainable work prerequisites. However, this dimension of social sustainability is less studied than economic and ecological sustainability. This paper addresses how sustainable work is considered in an entrepreneurial startup carrying out a greenfield project within a new industrial domain. Data were collected for 30 months in a longitudinal case study. The study shows that (i) working conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
1
23
0
1
Order By: Relevance
“…Although improving working conditions was rarely the main motivation for farmers to adopt agri-environmental practices, they played an important role in improving the quality of working conditions. Sustainable work encompasses all three dimensions of sustainability: economic, environmental, and social (Harlin and Berglund, 2021 ). Harlin and Berglund conducted a longitudinal study of how new (start-up) companies address the challenges of work and ensuring SS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although improving working conditions was rarely the main motivation for farmers to adopt agri-environmental practices, they played an important role in improving the quality of working conditions. Sustainable work encompasses all three dimensions of sustainability: economic, environmental, and social (Harlin and Berglund, 2021 ). Harlin and Berglund conducted a longitudinal study of how new (start-up) companies address the challenges of work and ensuring SS.…”
Section: Resultsmentioning
confidence: 99%
“…All these elements of decent work represent sources of personal resilience to possible factors of the labor market and social systems over which the individual has no control (Mushfiqur et al, 2018;Conigliaro, 2021), thus making a lasting contribution to an individual's positive career. Meaningful work, on the other hand, is a concept associated in the reviewed literature with the characteristics of work and organizational context that convey to 2021), Harlin and Berglund (2021) the worker that the goals and effects of the individual's work and the functioning of the organization are aligned with the overall social good (Sun et al, 2019). The construct of sustainable work is linked to the construct of decent and meaningful work.…”
Section: Job/work-focused Fields Of Study and Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection also included five open interviews carried out with the union stakeholders, as well as studies of firm documents, primarily PowerPoint presentations and internal meeting minutes. This case study was part of a larger research project with a mission to follow-up learnings from a start-up in early phases, hence, a new firm´s major greenfield project within a new industrial domain, as reported in Harlin and Berglund (2020).…”
Section: Total 21mentioning
confidence: 99%
“…Crucial elements for achieving sustainable change processes are three-party collaboration between the government, companies, and unions, as identified in a Scandinavian context (Brulin & Svensson, 2016). However, there is a gap in the literature on stakeholder collaboration that is focussed on sustainable work during industrial start-ups (Harlin & Berglund, 2020). Some obstacles for operationalisation of sustainable work dimensions (as part of social sustainability) during industrial development phases are that these dimensions are fuzzy and not clearly defined (Vallance et al, 2011).…”
Section: Introductionmentioning
confidence: 99%